Website Management as Public Information Media in Bogor Regency Government - Anisa Diniati; Intan Dara Phonna; Hanna Wisudawaty; Martha Tri Lestari (Warta Ikatan Sarjana Komunikasi Indonesia, 2025)
Abstract - Websites are widely employed in its use as a way of delivering targeted information, such as the use of websites in government organizations aimed at distributing integrated information. The information will be published on the official government website so that the public may obtain all vital government information. Researchers picked online media websites because Bogor Regency is highly active and constant in distributing information in the form of increasingly diverse material every day. The purpose of this research is to define the Bogor Regency Government's plan for administering the bogorkab.go.id website. The website is an attempt to address public information demands, particularly those of the Bogor Regency government. The reference concept employed refers to the components that must be addressed in identifying the major message that government agencies aim to transmit through their social media initiatives, namely: Character, major Purpose, Main Motive, Main Story, and Details. The results indicated that in a month, this one regional apparatus website could post more than 140 materials regarding the Regent's operations and policies in the form of YouTube videos, pictures, and COVID-19 infographics, which were also shared on social media. The uploaded news material also demonstrates that the information given by Bogor Regency as the Regent's centralized official media is simple to grasp and diverse from numerous views, fields, and concerns in the Bogor Regency region. Keywords: Digital Media, Digital Media Management, Information Media, Website Management, Bogor Regency Goverment